2019
DOI: 10.3892/etm.2019.8219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracoronary nicorandil before stent deployment in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: The present study aimed to clarify the effect of bolus intracoronary nicorandil on inflammatory, oxidative and adherent indicators in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). This randomized controlled trial (RCT) was performed to detect the inflammation and oxidative stress in intracoronary blood both before and after PCI. In total, 65 consecutive patients undergoing PCI were classified into a nicorandil therapy group (n=32) or a placebo group (n=33). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…24 , 25 Previous research found that an intracoronary bolus of nicorandil could improve the instantaneous increases of inflammation and oxidative stress in the coronary blood of patients with ACS during PCI. 21 This investigation demonstrated that an intracoronary injection of nicorandil could further ameliorate the inflammatory and oxidative reactions in peripheral blood, which supported the need for a longer treatment period for nicorandil.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…24 , 25 Previous research found that an intracoronary bolus of nicorandil could improve the instantaneous increases of inflammation and oxidative stress in the coronary blood of patients with ACS during PCI. 21 This investigation demonstrated that an intracoronary injection of nicorandil could further ameliorate the inflammatory and oxidative reactions in peripheral blood, which supported the need for a longer treatment period for nicorandil.…”
Section: Discussionmentioning
confidence: 56%
“… 20 On the other hand, ROS were generated and released after reperfusion because of damage of the mitochondrial respiratory chain. 21 The accumulation of ROS in the body caused oxidative damage, which may further aggravate MNR. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) induces coronary injury on the endothelial cells which is related to the proinflammatory response and oxidative stress. PCI increases the levels of the inflammatory response and pathophysiological levels of oxidative stress response, which promotes the progression of coronary restenosis in patients with coronary artery disease after PCI [46,47]. Coronary atherosclerotic lesion formation is related to oxidative stress and inflammatory response.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…52 The anti-inflammatory antioxidant property of nicorandil protected the coronary endothelial cell injury in patients undergoing percutaneous coronary intervention 53 and reduced the incidence of death following acute myocardial infarction. 54 In a direct cardiac tissue effect, nicorandil protected the heart against doxorubicin-induced cardiotoxicity. Nicorandil fixed the doxorubicin-impaired NO bioavailability and NF-kB activation and the resulted apoptosis and consequently improved cardiac functions and the myocardial histological picture.…”
Section: Ardiova Scul Ar Manife S Tation In Covid -19 and The Susmentioning
confidence: 99%
“…The anti‐inflammatory antioxidant property of nicorandil protected the coronary endothelial cell injury in patients undergoing percutaneous coronary intervention 53 and reduced the incidence of death following acute myocardial infarction 54 . In a direct cardiac tissue effect, nicorandil protected the heart against doxorubicin‐induced cardiotoxicity.…”
Section: Cardiovascular Manifestation In Covid‐19 and The Suspected Rmentioning
confidence: 99%